Do outside directors with government experience create value? - Kang, Jun-Koo (2019)
We examine whether outside directors with government experience add value to their firms. We find that government directors are more likely to miss board meetings and that their appointment announcements are greeted more negatively. Firms with government directors also experience poorer operating performance and more negative merger announcement returns, although their mergers are less likely to be challenged by antitrust authorities. These adverse valuation effects are largely alleviated when firms have large government sales, when they operate in regulated industries, or when government directors are politically connected. Using close gubernatorial election outcomes as a natural experiment and an instrumental variables approach to control for endogeneity bias do not change the results.